2017
DOI: 10.1242/dmm.030916
|View full text |Cite
|
Sign up to set email alerts
|

Chronic psychosocial stress disturbs long-bone growth in adolescent mice

Abstract: Although a strong association between psychiatric and somatic disorders is generally accepted, little is known regarding the interrelationship between mental and skeletal health. Although depressive disorders have been shown to be strongly associated with osteoporosis and increased fracture risk, evidence from post-traumatic stress disorder (PTSD) patients is less consistent. Therefore, the present study investigated the influence of chronic psychosocial stress on bone using a well-established murine model for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 63 publications
3
24
0
1
Order By: Relevance
“…Moreover, CSC mice display increased anxiety-related behavior (9) and increased myelopoiesis in the bone marrow (10). Importantly, we further revealed recently that cartilage-to-bone transition during growth plate endochondral ossification is disturbed in CSC versus single-housed control (SHC) mice and that catecholamines released locally in the bone marrow might underlie these negative stress consequences (11). As the process of secondary bone healing after fracture mimics the endochondral ossification process during longitudinal bone growth, we hypothesize that CSC exposure might also compromise bone fracture healing.…”
mentioning
confidence: 66%
“…Moreover, CSC mice display increased anxiety-related behavior (9) and increased myelopoiesis in the bone marrow (10). Importantly, we further revealed recently that cartilage-to-bone transition during growth plate endochondral ossification is disturbed in CSC versus single-housed control (SHC) mice and that catecholamines released locally in the bone marrow might underlie these negative stress consequences (11). As the process of secondary bone healing after fracture mimics the endochondral ossification process during longitudinal bone growth, we hypothesize that CSC exposure might also compromise bone fracture healing.…”
mentioning
confidence: 66%
“…As previously proposed [ 38 ], the most obvious candidate system to mediate crosstalk between the left and right limbs is the nervous system. While the exact mechanism remains to be determined, a recent study showed that peripheral sympathetic nerves might inhibit bone growth in response to sustained social stress [ 40 ]. Regardless of the mechanism, these results suggest that the observed systemic growth reduction in ePit-Col-p21 embryos is a combination of 2 effects: reduced growth efficiency of the contralateral bones in response to the left-specific insult, and impairment of placental function that affects the rest of the body.…”
Section: Discussionmentioning
confidence: 99%
“…Tibia lengths were assessed using a digital precision caliper. Left femurs were subjected to μCT analysis as described previously ( Foertsch et al, 2017 ). Briefly, scanning was done at 50 kV and 200 mA, voxel resolution was set to 8 μm.…”
Section: Methodsmentioning
confidence: 99%
“…The “chronic subordinate colony housing” (CSC) paradigm is a well-characterized animal model for PTSD in male mice ( Reber et al, 2016a ) and causes chronic low-grade inflammation ( Langgartner et al, 2018 ), disturbance of bone homeostasis ( Foertsch et al, 2017 ), general and social anxiety ( Slattery et al, 2012 ; Langgartner et al, 2017 ), and, in the presence of colonic pathobionts like Helicobacter spp. ( Langgartner et al, 2017 ), spontaneous colitis ( Reber et al, 2007 , 2011 , 2016b ; Langgartner et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%